Rendering in scattering media - Ren, Zhong; Zhou, Kun; Lin, Steve; Guo, Baining (2008)
Techniques are described for rendering a volume of scattering media, in particular by computing radiances of points or voxels in the scattering media. A set of sample points in the scattering media are found. Radiances of the sample points are computed. Radiance gradients of the sample points are computed from the radiances. The radiances and gradients are used to interpolate radiances throughout the scattering media. The set of sample points may be computed in an iterative dynamic manner in order to concentrate samples near features (e.g., shadow edges) of the scattering media.
US Patent 20100085360 A1